Preparation method and application of Ni / S co-doped hollow carbon spheres for producing hydrogen peroxide through efficient electro-catalysis oxygen reduction reaction

By using materials such as dopamine hydrochloride, thiourea and polystyrene microspheres in the 2e-ORR electrocatalyst, Ni/S co-doped hollow carbon spheres are prepared, which solves the problems of low catalytic activity and low selectivity of existing electrocatalysts, and achieves the effect of efficient electrocatalytic ORR production of H2O2.

CN119530823APending Publication Date: 2025-02-28HENAN NORMAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311113134.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing 2e-ORR electrocatalysts have low catalytic activity and low selectivity of 2e-path, making it difficult to efficiently electrocatalyze ORR production of H2O2.

Method used

Dopamine hydrochloride is used as the carbon precursor, thiourea is used as the S atom dopant, and polystyrene microspheres are used as the self-sacrificial template. The high-efficiency Ni/S co-doped hollow carbon spheres are prepared as cathode catalytic material by surface one-pot synthesis method and pyrolysis.

Benefits of technology

The 2e-ORR catalytic performance of Ni/S co-doped hollow carbon spheres in alkaline electrolytes was significantly improved, reaching 91.3% H2O2 selectivity, 99.6% @0.5V Faraday efficiency and 36h electrocatalytic stability, which was better than the hollow honeycomb carbon-based samples loaded with Ni.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530823A_ABST
    Figure CN119530823A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of Ni / S co-doped hollow carbon spheres for producing H2O2 through efficient electro-catalysis ORR. The preparation method comprises the following specific steps: dispersing polystyrene microspheres, nickel nitrate hexahydrate, thiosemicarbazide and dopamine hydrochloride into a tris (hydroxymethyl) aminomethane buffer solution to obtain a mixed solution; performing centrifugation, washing, drying and drying treatment to obtain precursor powder; and carrying out high-temperature calcination on the precursor under the protection of N2, cooling to room temperature, and carrying out acid leaching, water washing and drying on the product to obtain the Ni / S co-doped hollow carbon spheres. Benefited from the regulation and control effect of doped S on an Ni atom electronic structure and the synergistic effect of a hollow structure with a high specific surface area, the Ni / S co-doped hollow carbon sphere has extremely high H2O2 selectivity and excellent catalytic activity in an alkaline 2e-ORR process, and shows high H2O2 yield and Faraday efficiency in an electrocatalytic H2O2 production test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparing non-precious metal-doped hollow multi-level porous carbon by a template-assisted method, and specifically relates to a preparation method of a honeycomb Ni / S co-doped hollow carbon catalytic hydrogen peroxide production electrocatalyst constructed by a polystyrene microsphere-assisted method and its application in electrocatalytic ORR hydrogen peroxide production. Background Art

[0002] In order to cope with the current energy crisis and ecological environment problems, it has become a consensus in the academic community to develop and explore technologies that replace anthraquinone processes to produce hydrogen peroxide (H2O2). In the past, research on electrocatalytic oxygen reduction reaction (ORR) mainly focused on 4e - Until recently, with the development of electrocatalysts, electrochemical cells and membranes, electrochemical 2e - ORR production of H2O2 has returned to the stage and has gradually become a research hotspot due to the following advantages: (1) use of green and natural resources, no consumption of fossil fuels; (2) clean environment, no organic waste; (3) mild reaction conditions of ambient temperature and pressure; (4) avoidance of explosive gas environment by separating anode and cathode; (5) on-site power generation. Although the precious metal Pd-based catalysts show excellent 2e - ORR selectivity, but its scarcity of resources, high development costs and poor stability have seriously limited its large-scale application. Therefore, it is necessary to continue to develop and prepare 2e - ORR selective non-precious metal catalyst. Nickel has good adsorption capacity for O atoms and O2 molecules, but due to the inappropriate d-band center of Ni, its binding strength to oxygen-containing intermediates *OOH is poor, so Ni-based 2e - The performance of ORR electrocatalysts still needs to be further improved. In addition, in order to improve the apparent activity performance of the catalyst, it is necessary to perform certain structural designs on it. Among various material structures, hollow structures show obvious advantages in energy-related applications. Summary of the invention

[0003] The technical problem solved by the present invention is to provide a method for preparing Ni / S co-doped hollow carbon spheres with high efficiency electrocatalytic ORR to produce H2O2, so as to solve the existing 2e - ORR electrocatalyst has low catalytic activity and 2e - The present invention designs a high-performance Ni-based 2e -Starting from ORR electrocatalyst, dopamine hydrochloride (DA) was used as carbon precursor, thiosemicarbazide as S atom dopant, polystyrene (PS) microspheres as self-sacrificial templates, and a series of Ni / S co-doped hollow carbon spheres were synthesized by surface one-pot synthesis and pyrolysis. The prepared Ni / S co-doped hollow carbon spheres were used as cathode catalyst materials to test their electrocatalytic 2e - ORR selectivity.

[0004] The present invention adopts the following technical solution to solve the above technical problems, a method for preparing Ni / S co-doped hollow carbon spheres with high efficiency electrocatalytic ORR to produce H2O2, characterized by the specific steps of:

[0005] Step S1: Adding a metal source (nickel nitrate hexahydrate) solution into secondary water to obtain material A;

[0006] Step S2: dispersing the template polystyrene microspheres in anhydrous ethanol to obtain material B;

[0007] Step S3: mixing the material B obtained in step S2 with thiosemicarbazide, material A, dopamine hydrochloride and tris(hydroxymethyl)aminomethane buffer solution, stirring at room temperature for a certain period of time, and centrifuging, washing, drying and grinding the product to obtain material C;

[0008] Step S4: Transfer the material C obtained in step S3 to a tube furnace and heat it at room temperature at 2-4°C min under N2 gas protection. -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at this temperature for 0.5-2h, and then continued to rise at a rate of 5-10℃min -1 The temperature is raised to 500-900°C at a heating rate and kept at this temperature for 1-3 hours, and then naturally cooled to room temperature to obtain material D;

[0009] Step S5: The material D obtained in step S4 is impregnated with an acidic solution, washed with water, and dried to obtain Ni / S co-hollow carbon spheres, which are used as an electrocatalyst for efficient ORR production of H2O2.

[0010] Preferably, the template (polystyrene) in step S2 includes but is not limited to PS, silicon dioxide, etc., and the concentration of material A is 5-15wt%.

[0011] Preferably, the S source (semicarbazide) in step S3 includes but is not limited to sulfur-containing compounds such as sulfur powder, semicarbazide, and thiourea, the amount of nickel nitrate hexahydrate to semicarbazide is 1:0 to 1:10, and the amount ratio of nickel nitrate hexahydrate to dopamine hydrochloride is 1:2 to 1:24.

[0012] Preferably, the heat treatment process in step S4 is carried out at 2°C min -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min-1 The temperature was raised to 600 °C at a heating rate and kept at this temperature for 2 h.

[0013] Preferably, the acidic solution in step S5 has a substance concentration of 1 to 3 mol L -1 of hydrochloric acid solution, the pickling time is 12 to 24 hours.

[0014] The application of Ni / S co-doped hollow carbon spheres prepared by the method described in the present invention as cathode ORR electrocatalysts is characterized in that the specific process is: dispersing the Ni / S co-doped hollow carbon sphere catalyst in a mixed solution containing 5wt% Nafion solution, isopropanol and secondary water, dripping the uniform slurry obtained by ultrasonic treatment on one side of the waterproof layer of the conductive substrate, and using it as a cathode ORR H2O2 production electrocatalyst after natural drying.

[0015] Preferably, the conductive substrate is hydrophobic carbon paper or an electrode composite substrate of hydrophobic carbon paper, a waterproof film and nickel foam.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The semicarbazide used in the present invention is a strong ligand that can utilize the unbonded electron pairs of nitrogen atoms and sulfur atoms to react with metal Ni. 2+ Therefore, before the polymerization of dopamine monomer, Ni 2+ Ions and thiosemicarbazide make the two complex first, thereby increasing the nickel salt Ni 2+ Dispersibility enables the catalyst to provide more efficient active sites after pyrolysis.

[0018] 2. The highly electronegative S atoms doped in the present invention can significantly adjust the electronic structure of metal Ni. At the same time, the S atoms are embedded in the carbon matrix to form p-π conjugation. Due to their large atomic radius and strong polarity, they can enhance the spin density of neighboring carbon atoms and promote charge rearrangement. The two synergistically optimize the energy barrier of the active center Ni to form the *OOH intermediate, thus improving the 2e - Selectivity of ORR.

[0019] 3. The present invention uses PS microspheres as a self-sacrificial template, which can significantly improve the specific surface area and porous structure of the catalyst, thereby facilitating the catalytic process to expose more active sites, provide abundant material transmission channels, and improve the accessibility of active sites.

[0020] 4. The Ni / S co-doped hollow carbon spheres prepared by the present invention exhibit excellent 2e in alkaline electrolytes due to the regulation of the electronic structure of Ni atoms by doping S atoms and the synergistic effect of the hollow spherical shell structure with a high specific surface area. – ORR catalytic performance, 91.3% H2O2 selectivity, The H2O2 yield, Faradaic efficiency of 99.6%@0.5V and electrocatalytic stability for 36h are significantly better than those of the Ni-loaded hollow honeycomb carbon-based sample Ni@NCHS (H2O2% = ~68.7%, n = 2.63). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The middle is the SEM image of the material NiS6@NCHS prepared in Example 4;

[0022] Figure 2 Ni@NCHS, NiS2@NCHS, NiS6@NCHS and NiS prepared in Examples 1, 2, 4 and 6 10 @NCHS’s XRD pattern;

[0023] Figure 3 Nitrogen absorption / desorption curves of Ni@NCHS and NiS6@NCHS prepared in Examples 1 and 4;

[0024] Figure 4 The pore size distribution diagram of Ni@NCHS and NiS6@NCHS prepared in Examples 1 and 4;

[0025] Figure 5 LSV diagrams of Ni@NCHS and NiS6@NCHS prepared in Examples 1 and 4;

[0026] Figure 6 The electron transfer number diagram of Ni@NCHS and NiS6@NCHS prepared in Examples 1 and 4;

[0027] Figure 7 H2O2 selectivity diagram of Ni@NCHS and NiS6@NCHS prepared in Examples 1 and 4. DETAILED DESCRIPTION

[0028] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0029] Example 1

[0030] Step S1: Add a metal source (nickel nitrate hexahydrate) solution into secondary water to obtain a concentration of 0.1 mol L -1 Material A1;

[0031] Step S2: dispersing 8.0 g of template polystyrene microspheres in 91.0 mL of anhydrous ethanol to obtain material B1;

[0032] Step S3: Mix the material B1 obtained in step S2 with 890 μL of material A1, 1.6 mmol dopamine hydrochloride and 100 mL 0.1 mol L -1 The product was mixed with a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, stirred at room temperature for a certain period of time, and the product was centrifuged, washed, dried and ground to obtain material C1;

[0033] Step S4: The material C1 obtained in step S3 was transferred to a tube furnace and heated from room temperature to 2°C min -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min -1 The temperature was raised to 600°C at a heating rate and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain material D1;

[0034] Step S5: The material D1 obtained in step S4 was treated with 2 mol L -1 The electrocatalyst Ni@NCHS was obtained after immersion in the acidic solution for 12 h, filtration, water washing and drying.

[0035] Example 2

[0036] Step S1: Add a metal source (nickel nitrate hexahydrate) solution into secondary water to obtain a concentration of 0.1 mol L -1 Material A2;

[0037] Step S2: dispersing 8.0 g of template polystyrene microspheres in 91.0 mL of anhydrous ethanol to obtain material B2;

[0038] Step S3: The material B2 obtained in step S2 was mixed with 0.0162 g of thiosemicarbazide, 890 μL of material A2, 1.6 mmol of dopamine hydrochloride and 100 mL of 0.1 mol L -1 The product was mixed with a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, stirred at room temperature for a certain period of time, and the product was centrifuged, washed, dried and ground to obtain material C2;

[0039] Step S4: The material C2 obtained in step S3 was transferred to a tube furnace and heated from room temperature to 2°C min -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min -1 The temperature was raised to 600°C at a heating rate and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain material D2;

[0040] Step S5: The material D2 obtained in step S4 was treated with 2 mol L -1 After immersion in acidic solution for 12 h, filtration, water washing and drying, Ni / S co-doped hollow carbon spheres NiS2@NCHS were obtained.

[0041] Example 3

[0042] Step S1: Add a metal source (nickel nitrate hexahydrate) solution into secondary water to obtain a concentration of 0.1 mol L -1 Material A3;

[0043] Step S2: dispersing 8.0 g of template polystyrene microspheres in 91.0 mL of anhydrous ethanol to obtain material B3;

[0044] Step S3: The material B3 obtained in step S2 was mixed with 0.0324 g of thiosemicarbazide, 890 μL of material A3, 1.6 mmol of dopamine hydrochloride and 100 mL of 0.1 mol L -1 The product was mixed with a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, stirred at room temperature for a certain period of time, and the product was centrifuged, washed, dried and ground to obtain material C3;

[0045] Step S4: The material C3 obtained in step S3 is transferred to a tube furnace and heated from room temperature to 2°C min -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min -1 The temperature was raised to 600°C at a heating rate and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain material D3;

[0046] Step S5: The material D3 obtained in step S4 was treated with 2 mol L -1 After immersion in acidic solution for 12 h, filtration, water washing and drying, Ni / S co-doped hollow carbon spheres NiS4@NCHS were obtained.

[0047] Example 4

[0048] Step S1: Add a metal source (nickel nitrate hexahydrate) solution into secondary water to obtain a concentration of 0.1 mol L -1 Material A4;

[0049] Step S2: dispersing 8.0 g of template polystyrene microspheres in 91.0 mL of anhydrous ethanol to obtain material B4;

[0050] Step S3: The material B4 obtained in step S2 was mixed with 0.0486 g of thiosemicarbazide, 895 μL of material A4, 1.6 mmol of dopamine hydrochloride and 100 mL of 0.1 mol L -1 The product was mixed with a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, stirred at room temperature for a certain period of time, and the product was centrifuged, washed, dried and ground to obtain material C4;

[0051] Step S4: The material C4 obtained in step S3 was transferred to a tube furnace and heated from room temperature to 2°C min -1The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min -1 The temperature was raised to 600°C at a heating rate and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain material D4;

[0052] Step S5: The material D4 obtained in step S4 was treated with 2 mol L -1 After immersion in acidic solution for 12 h, filtration, water washing and drying, Ni / S co-doped hollow carbon spheres NiS6@NCHS were obtained.

[0053] Example 5

[0054] Step S1: Add a metal source (nickel nitrate hexahydrate) solution into secondary water to obtain a concentration of 0.1 mol L -1 Material A5;

[0055] Step S2: dispersing 8.0 g of template polystyrene microspheres in 91.0 mL of anhydrous ethanol to obtain material B5;

[0056] Step S3: The material B5 obtained in step S2 was mixed with 0.0648 g of thiosemicarbazide, 890 μL of material A5, 1.6 mmol of dopamine hydrochloride and 100 mL of 0.1 mol L -1 The product was mixed with a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, stirred at room temperature for a certain period of time, and the product was centrifuged, washed, dried and ground to obtain material C5;

[0057] Step S4: The material C5 obtained in step S3 was transferred to a tube furnace and heated from room temperature to 2°C min -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min -1 The temperature was raised to 600°C at a heating rate and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain material D5;

[0058] Step S5: The material D5 obtained in step S4 was treated with 2 mol L -1 After immersion in acidic solution for 12 h, filtration, water washing and drying, Ni / S co-doped hollow carbon spheres NiS8@NCHS were obtained.

[0059] Example 6

[0060] Step S1: Add a metal source (nickel nitrate hexahydrate) solution into secondary water to obtain a concentration of 0.1 mol L -1 Material A6;

[0061] Step S2: dispersing 8.0 g of template polystyrene microspheres in 91.0 mL of anhydrous ethanol to obtain material B6;

[0062] Step S3: The material B6 obtained in step S2 was mixed with 0.0810 g of thiosemicarbazide, 890 μL of material A6, 1.6 mmol of dopamine hydrochloride and 100 mL of 0.1 mol L -1 The product was mixed with a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5, stirred at room temperature for a certain period of time, and the product was centrifuged, washed, dried and ground to obtain material C6;

[0063] Step S4: The material C6 obtained in step S3 was transferred to a tube furnace and heated from room temperature to 2°C min -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min -1 The temperature was raised to 600°C at a heating rate and kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain material D6;

[0064] Step S5: The material D6 obtained in step S4 was treated with 2 mol L -1 After immersion in acidic solution for 12 h, filtration, water washing and drying, Ni / S co-doped hollow carbon spheres NiS 10 @NCHS.

[0065] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and the specification only illustrate the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing Ni / S co-doped hollow carbon spheres for producing hydrogen peroxide by highly efficient electrocatalytic oxygen reduction reaction, characterized in that The specific steps are: Step S1: Adding a metal source solution to secondary water to obtain material A; Step S2: dispersing the template polystyrene microspheres in anhydrous ethanol to obtain material B; Step S3: mixing the material B obtained in step S2 with thiosemicarbazide, material A, dopamine hydrochloride and tris(hydroxymethyl)aminomethane buffer solution, stirring at room temperature for a certain period of time, and centrifuging, washing, drying and grinding the product to obtain material C; Step S4: Transfer the material C obtained in step S3 to a tube furnace and heat it at room temperature at 2-4°C min-1 under N2 gas protection. -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at this temperature for 0.5-2h, and then continued to rise at a rate of 5-10℃min -1 The temperature is raised to 500-900°C at a heating rate and kept at this temperature for 1-3 hours, and then naturally cooled to room temperature to obtain material D; Step S5: The material D obtained in step S4 is impregnated with an acidic solution, washed with water, and dried to obtain Ni / S co-hollow carbon spheres, which are used as a high-efficiency electrocatalytic ORR catalyst for producing H2O2.

2. The Ni / S co-doped hollow carbon sphere electrocatalyst for high efficiency ORR production of H2O2 according to claim 1, characterized in that: The template in step S2 includes but is not limited to polystyrene, silicon dioxide, etc., and the concentration of material A is 5-15wt%.

3. The Ni / S co-doped hollow carbon spheres for high-efficiency electrocatalytic ORR production of H2O2 according to claim 1, characterized in that: The S source in step S3 includes but is not limited to sulfur-containing compounds such as thiosemicarbazide, sulfur powder, and thiourea. The amount of nickel nitrate hexahydrate to thiosemicarbazide is 1:0 to 1:10, and the amount ratio of nickel nitrate hexahydrate to dopamine hydrochloride is 1:2 to 1:

24.

4. The Ni / S co-doped hollow carbon spheres for high-efficiency electrocatalytic ORR production of H2O2 according to claim 1, characterized in that: The heat treatment process in step S4 is 2°C min -1 The temperature was raised to 350℃ at a rate of 100℃ and kept at that temperature for 1h, and then continued to rise at a rate of 5℃min -1 The temperature was raised to 600 °C at a heating rate and kept at this temperature for 2 h.

5. The Ni / S co-doped hollow carbon spheres for high-efficiency electrocatalytic ORR production of H2O2 according to claim 1, characterized in that: The acidic solution in step S5 has a substance concentration of 1 to 3 mol L -1 of hydrochloric acid solution, the pickling time is 12 to 24 hours.

6. Use of Ni / S co-doped hollow carbon spheres prepared by the method according to any one of claims 1 to 5 as cathode oxygen reduction electrocatalysts, characterized in that The specific process is: the Ni / S co-doped hollow carbon sphere catalyst is dispersed in a mixed solution containing 5wt% Nafion solution, isopropanol and secondary water, and the uniform slurry obtained by ultrasonic treatment is drop-coated on one side of the waterproof layer of the conductive substrate, and after natural drying, it is used as the cathode ORR H2O2 production electrocatalyst.

Citation Information

Cited By

  • Preparation method of catalyst for preparing hydrogen peroxide through electro-catalysis as well as product and application of catalyst

    CN116623214A

  • A method for preparing a catalyst for electrocatalytic preparation of hydrogen peroxide and products and uses thereof

    CN116623214B